Culinary Linguistic Approach in Naming Simalungun Traditional Food - Bako, Evi Novalin; Mulyadi, Mulyadi (Randwick International of Education and Linguistics Science Journal, 2024)
This research concerned with words belonging to the naming process of the traditional culinary of Simalungun This research using a qualitative descriptive method with a phenomenological perspective. The data is in the form of a lexicon of traditional Simalungun culinary names. Data sources were obtained from Simalungun native speakers in Simalungun area, namely Pematang Raya, Saribu Dolok, Siantar and Tanah Jawa. The results of this research found four types of naming traditional Simalungun culinary delights, namely: 1) naming based on characteristics: dayok nabinatur and nitak gabur-gabur, 2) naming based on the main ingredients: Hinasumba, Sibak, Labar, Obbut, 3) naming based on the term: namalum and 4) naming based on processing method: Tinuktuk.